2011
DOI: 10.1111/j.1524-4725.2010.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Intense Pulsed Light in the Treatment of Riehl's Melanosis

Abstract: The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…Our finding suggests that the hyperpigmentation is because of increased melanin in the dermis, which possibly originates from the epidermis because of injury to the basal cells. Riehl melanosis, also known as pigmented contact dermatitis, seems to be associated with friction or contact dermatitis . In this study, the etiology of several cases of pigmentary incontinence was friction or contact dermatitis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our finding suggests that the hyperpigmentation is because of increased melanin in the dermis, which possibly originates from the epidermis because of injury to the basal cells. Riehl melanosis, also known as pigmented contact dermatitis, seems to be associated with friction or contact dermatitis . In this study, the etiology of several cases of pigmentary incontinence was friction or contact dermatitis.…”
Section: Discussionmentioning
confidence: 53%
“…Riehl melanosis, also known as pigmented contact dermatitis, seems to be associated with friction or contact dermatitis. 10,11 In this study, the etiology of several cases of pigmentary incontinence was friction or contact dermatitis. We infer that pigmentary incontinence in PIH might have a similar pathophysiology as Riehl melanosis.…”
Section: Discussionmentioning
confidence: 80%
“…Clinically, melanin pigment in upper dermis is so slowly absorbed that the hyperpigmentation appears to persist or worsen over time if consistent contact of possible allergens happens (17). Riehl’s melanosis, first described by Riehl as “war melanosis” in 1917, similarly affects the face, and is related with nutritional factors and sensitizing chemicals in cosmetics (181920). Riehl’s melanosis is considered synonymous with PCD, with the common allergen being fragrances and chemicals in cosmetics (19).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [25] published recently a work on the effi cacy and safety of an IPL device (Lumenis One; Lumenis, Santa Clara, CA, USA; 590-/640-/ 695-nm cut-off fi lters; fl uence, 11 -17 J/cm 2 , with triplepulse mode; pulse width, 3 -4 ms; delay time, 35 -40 ms) in the treatment of Riehl melanosis in a split-face study of six patients (Fitzpatrick skin type IV). In terms of histological analysis, the authors reported signifi cantly fewer melanin granules and melanophages in the treated side as compared with the control side after 10 IPL sessions.…”
Section: Pigmented Lesionsmentioning
confidence: 99%
“…Haddad et al [64] evaluated the effect of increasing the fl uence (20,25,40, and 50 J/cm 2 ) of an IPL device on the outcome of ALA-PDT (single treatment, 2-h incubation) in 24 patients with AK and photodamaged skin. The assessment 8 weeks after treatment indicated that AK clearance improved with increasing fl uence.…”
Section: Pdt Of Nonmelanoma Skin Cancermentioning
confidence: 99%